TO THE QUESTION OF LEGAL POSITIONSTATE AUTHORITIES REGULATINGCONFLICT RESOLUTION IN A DEMOCRATIC STATE (Journal of actual problems of jurisprudence, 2019)
This article focuses on the role and functions of State bodies, judges and prosecutors in resolving conflicts in society.